2017
DOI: 10.1016/j.adengl.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitiligo on Quality of Life

Abstract: Vitiligo has a minimal impact on the QOL of our patients. QOL was worse in patients with genital lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 25 publications
6
41
0
Order By: Relevance
“…Low self-esteem and selfreports of social isolation due to feelings of shame have been reported by many patients with vitiligo [41]. Moral et al have reported a rate of depression as 34%, according to BDI and anxiety as 60%, according to BAI, in their sample [71]. In his 2013 study, Manzoni has also reported higher levels of anxiety and depression, compared to that observed in general population, in parents of children from all interior-dermatosis groups (atopic dermatitis, psoriasis, and vitiligo -26% depression and 42% anxiety) [72].…”
Section: Discussionmentioning
confidence: 99%
“…Low self-esteem and selfreports of social isolation due to feelings of shame have been reported by many patients with vitiligo [41]. Moral et al have reported a rate of depression as 34%, according to BDI and anxiety as 60%, according to BAI, in their sample [71]. In his 2013 study, Manzoni has also reported higher levels of anxiety and depression, compared to that observed in general population, in parents of children from all interior-dermatosis groups (atopic dermatitis, psoriasis, and vitiligo -26% depression and 42% anxiety) [72].…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis study pooled data on 1080 patients with vitiligo and found that at least one in four vitiligo patients were diagnosed with a form of clinical depression when using a validated screening questionnaire . A cross‐sectional study of 150 patients with vitiligo reported high prevalences of depression (34%) and anxiety (60%) . A retrospective study of 31 adults with vitiligo found increased occurrence of 3+ uncontrollable events, decreased perceived social support and increased anxiety in vitiligo compared to 116 other dermatologic disease controls .…”
Section: Discussionmentioning
confidence: 99%
“…14 A cross-sectional study of 150 patients with vitiligo reported high prevalences of depression (34%) and anxiety (60%). 15 A retrospective study of 31 adults with vitiligo found increased occurrence of 3+ uncontrollable events, decreased perceived social support and increased anxiety in vitiligo compared to 116 other dermatologic disease controls. 16 A cross-sectional study of 30 Indian patients with vitiligo found that 10% had thoughts of suicide, and 3.3% had attempted suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo -any type concerned -casts significant impacts on the quality of life (QOL) of patients [1]. The presence of lesions on the visible parts and the extensiveness of lesions was reported to be significantly associated with impairments in QOL [3].…”
Section: Discussionmentioning
confidence: 99%
“…Generalised vitiligo (GV) is a disfiguring disease affecting the self image, daily life, and many social issues of sufferers [1]. We have previously reported on the application of digital epiluminescence dermoscopy (DED) in detecting the sparing of perifollicular pigments in localised vitiligo [2].…”
Section: Introductionmentioning
confidence: 99%